Media education and educational commons for youth civic engagement. A case study from the Horizon 2020 project SMOOTH - Cappello, Gianna; Siino, Marianna (Frontiers in Sociology, 2023)
This article reports the preliminary findings of the first implementation round of a case study included in the Horizon project SMOOTH which aims to introduce and study the emergent paradigm of the educational commons as an alternative value and action system to reinforce intercultural and intergenerational dialogue, establishing spaces of democratic citizenship that support local communities’ development. The case study adopts this paradigm in conjunction with insights derived from the field of media education, digital commons and “participatory culture”. The experimental media education activities implemented during the case study intend to encourage youths to develop the skills, knowledge, and ethical and critical frameworks needed to express a “civic intentionality” and be fully “engaged citizens” in the digital public sphere. Fieldwork, framed with an ethnographic and action-research approach, was developed through the investigation of the three dimensions of the notion of educational commons (commoners, commoning practices, and the community). Our research questions were: (a) how young people collectively experience and construct the commons in educational settings; (b) how young people and adults in the educational community experience peer governance and how they manage and resolve conflicts within the community they belong to; (c) how the co-creation of a photo-blog as a shared space of work, enables young people to discover and develop civic intentionality in the digital public sphere; (d) what are the effects of applying a commons’ logic to address inequalities and achieve social inclusion of young people from vulnerable social groups.